Comparative analysis of pectic polysaccharides isolated from various thinned young red-fleshed kiwifruits: Structural properties and biological functions - Jing-Liu He; Kai-Xin Jiang; Ting Wei; Jin-Lei Geng; Zi-Fan Zhao; Jing Feng; Jie Li; Hong-Yan Liu; Shang Lin; Ding-Tao Wu (Food Chemistry: X, 2025)
To utilize thinned young kiwifruit for potential industrial applications, this study compared structural properties and in vitro bioactivities of pectic polysaccharides isolated from three thinned young red-fleshed kiwifruit cultivars, including Actinidia chinensis cv. ‘Donghong’, ‘Hongshi’, and ‘Hongyang’. The results demonstrated that these young kiwifruit byproducts were rich in pectic polysaccharides, with extraction yields of 90.7–101.3 mg/g dry weight. Although their bound polyphenols (8.02–8.93 mg GAE/100 mg), esterification degrees (50.45–61.32 %), and molecular weights (7.44 × 104–8.51 × 104 Da) varied across cultivars, the glycosidic linkage patterns showed remarkable consistency, dominated by homogalacturonan (12.07–13.84 mol%) and rhamnogalacturonan-I (70.25–75.09 mol%) regions. Notably, all these pectic polysaccharides, particularly those isolated from the ‘Donghong’ cultivar, demonstrated notable antioxidant, antiglycation, prebiotic, and immunoenhancing activities in vitro. These findings indicate that thinned red-fleshed kiwifruit byproducts are rich sources of RG-I enriched pectic polysaccharides, with significant potential as functional food ingredients.